2016
DOI: 10.21149/spm.v58i4.8021
|View full text |Cite
|
Sign up to set email alerts
|

Subestimación de la mortalidad causada por el tránsito en México:análisis subnacional

Abstract: 412salud pública de méxico / vol. 58, no. 4, julio-agosto de 2016 Pérez-Núñez R y col. Subestimación de la mortalidad causada por el tránsito en México: análisis subnacionalRicardo Pérez-Núñez, D en CS, (1) Mariana G Mojarro-Íñiguez, MC Part, M en CS, (2) Ma. Eulalia Mendoza-García, L en Soc,Sergio Rodrigo Rosas-Osuna, MC Part, M en Admon Sist Salud, (1) Martha Híjar, D en C.((1) Secretariado Técnico del Consejo Nacional para la Prevención de Accidentes. México, Distrito Federal.(2) Investigadora independie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 10 publications
(10 reference statements)
0
3
1
5
Order By: Relevance
“…The data presented here do not recall previous exercises on the underestimation of road traffic mortality, thus the results presented here should be taken with caution 11 , 12 . For example, the results presented in this paper show that Veracruz is fulfilling its established goal, when in fact the actual value could be higher than observed given the large number of deaths allocated to unspecified codes or “garbage codes”.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The data presented here do not recall previous exercises on the underestimation of road traffic mortality, thus the results presented here should be taken with caution 11 , 12 . For example, the results presented in this paper show that Veracruz is fulfilling its established goal, when in fact the actual value could be higher than observed given the large number of deaths allocated to unspecified codes or “garbage codes”.…”
Section: Discussioncontrasting
confidence: 73%
“…The first one is due to actions linked to the Mexican Road Safety Initiative which have been set since 2008 in Mexico, before the Decade of Action, which could have affected the trend that was observed in the previous period and influenced the establishment of national and state goals. The second one is due to the decrease observed in 2007, which, as documented 11 , 12 , could be more related to problems in the recording of information that affected this year than to a real decrease in mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) estimates they represent the leading cause of death among young people of 15 to 29 years of age. 5,6 In Spain, approximately 10 % of hospitalizations between 2004 and 2008 were calculated to derive from ECIs associated with the use of motor vehicles. 7 One study carried out in Colombia found that, between January 2004 and December 2007, there were 12 148 patients with ECI, out of which 37.1 % were younger than 18 years; when the injury occurred in the street, 29 % of injured were pedestrians, 44.3 % were drivers and 24.1 %, passengers.…”
Section: Introductionmentioning
confidence: 99%
“…En México, las LTC son la quinta causa de muerte prematura más frecuente (Institute for Health Metrics and Evaluation, 2016). Cada año se registran 16 mil defunciones por LTC en nuestro país, de las cuales 4,364 corresponden a peatones (Secretariado Técnico del Consejo Nacional para la Prevención de Accidentes, 2016), pese a los datos, se estima que la cifra podría ser mayor (Pérez, Híjar, Celis e Hidalgo, 2012;Pérez, Mojarro, Mendoza, Rosas e Híjar, 2016).…”
unclassified